POTENSI DAN PERAN MASYARAKAT DALAM EKONOMI KREATIF BERBASIS SUMBER DAYA LOKAL DI DESA PUUNGKOILU KEC. BUNGKU TENGAH KABUPATEN MOROWALI - Salma D; Anisah Anisah; Ni Luh Putu Evvy Rossanty; Siti Nurmin (Jurnal Abdimas Bina Bangsa, 2023)
Empowering the community through creative economic activities is considered suitable to be applied in developing the economic sector in order to realize the welfare of the Puungkoilu Village community. Based on the analysis of the problem situation, it has been found that the potential and role of the community in the economy based on local resource utilization have not been optimized. Therefore, the goal of this service activity is to enhance the potential and role of the community in locally-based creative economy using local resources in Puungkoilu Village. The implementation of the activity involves three stages: (1) preparation stage, (2) implementation stage, and (3) evaluation stage. The results of the socialization, training, and mentoring activities in locally-based creative economy can enhance the potential and role of the community in the locally-based creative economy in Puungkoilu Village. Furthermore, community engagement activities like this should continue in Puungkoilu Village, considering the numerous local resource potentials that can be maximized, such as potentials in the agricultural and plantation sectors, as well as inviting practitioners who are relevant to these fields